Evaluating the sources and fate of nitrate in riparian aquifers under agricultural land using in situ-measured noble gases, stable isotopes, and metabolic genes. (1st March 2023) - Ju, YeoJin; Koh, Dong-Chan; Kim, Dong-Hun; Mayer, Bernhard; Kwon, Hong-il
Highlights: Nitrate in groundwater was mainly derived from manure and sewage. Recharge of anoxic paddy soil water contributed to natural attenuation of NO3 – . Abundance of metabolic genes implied prevalence of bacteria-mediated NO3 – attenuation. In-situ measured gases revealed loss of dissolved biogenic N2(g) to the atmosphere. Nitrate attenuation reduced NO3 – flux from aquifer to stream by up to 26 N kg/ha/y. Abstract: Riparian zones with their buffering ability and abundant water supply are often subjected to intensive agricultural activities. We investigated a riparian aquifer located near a stream in South Korea that recently experienced sharply decreasing groundwater levels and elevated nitrate (NO3 – ) concentrations, which were attributed to local agricultural activities. Our goal was to identify the predominant nitrogen sources and NO3 – removal processes. Multiple approaches including geochemical and isotopic tracers, land-use analysis, metabolic gene quantification, and inert gas tracers were used to elucidate groundwater and nutrient dynamics in stream-side granitic aquifers. The dual isotopic composition of NO3 – identified manure and sewage as the major sources of NO3 – contamination. Denitrification was the dominant NO3 – removal process in the aquifer, as demonstrated by the negative relationship between δ 15 N and δ 18 O values in NO3 – and NO3 – /Cl – . Denitrification and anammox genes were also observed in microbial communities of the aquifer throughout the study site, suggesting that these processes support effective natural NO3 – attenuation in groundwater. A mixing model constructed using a catchment-scale dataset including SiO2 concentrations and δ 18 O-H2 O suggested that mixing with paddy soil water was the major driver of denitrification in the aquifer at the study site, where impervious layers provided anaerobic conditions for natural NO3 – attenuation. Denitrification reduced the NO3 – flux into the nearby stream by up to 114.4 NO3 – kg/ha/y (26 kg N/ha/y). The N2 generated by denitrification did not accumulate in the groundwater, but mostly escaped from groundwater to the atmosphere, as demonstrated by the degassed signature of dissolved inert gases below the air saturated water level. This study identified the predominant NO3 – sources and conceptualized N cycling in the heavily developed agricultural riparian aquifer using multiple tracers, demonstrating that NO3 – is partially removed through denitrification and possibly anammox while N2 mostly escapes into the atmosphere. Graphical abstract: Image, graphical abstract